Pharmacoresistant Temporal Lobe Epilepsy Controlled by Bilateral Anterior Thalamic Nuclei Thalamotomy - Made Agus Mahendra Inggas; Retno Jayantri Ketaren; Vivien Puspitasari; Julianta Wahyoepramono (Eduvest - Journal of Universal Studies, 2025)
Introduction: Several potential targets have been suggested for the treatment of pharmacoresistant epilepsy, including medial parts of temporal lobes, caudate nucleus, cerebellum, centromedian nucleus of the thalamus, subthalamic nucleus and anterior thalamic nucleus (ATN). The effectiveness of bilateral ATN thalamotomy as treatment option for pharmacoresistant temporal lobe epilepsy is a considerable approach in this recent advances. Method: Case report. Result: A 24-year old male patient presented with unknown onset of generalized tonic clonic seizures and serials of drop attacks since 4 years of age. He was also diagnosed with Attention Defcit Hyperactivity Disorder (ADHD) and a history of febrile seizures. Brain MRI was normal. He has been treated with so many combination of antiepileptic drugs (AEDs) with last combination were Valproic acid 500 mg twice daily, Clonazepam 2 mg thrice daily and Zonisamide 100 mg twice daily. Despite all polytherapy AEDs given, he was still having recurrent seizures. Vagal Nerve Stimulation (VNS) was then conducted and seizures were slightly better. After maximal VNS voltage given, seizures became more frequent. ATN bilateral thalamotomy was done five years after, where seizure was better controlled. Levetiracetam 500mg twice daily and phenobarbital 15 mg once was given in concordance to the surgery, and the patient is doing well until now. Conclusion: In pharmacoresistant temporal lobe epilepsy where AEDs and VNS showed no signifcant improvement, ATN bilateral thalamotomy is considered to be a compelling treatment option. As we know, this is a first case report for ATN thalamotomy for epilepsy in south east asia region.